2017
DOI: 10.1158/0008-5472.can-17-0020
|View full text |Cite
|
Sign up to set email alerts
|

Spi-B–Mediated Silencing of Claudin-2 Promotes Early Dissemination of Lung Cancer Cells from Primary Tumors

Abstract: Dissociation from epithelial sheets and invasion through the surrounding stroma are critical early events during epithelial cancer metastasis. Here we find that a lymphocyte lineage-restricted transcription factor, Spi-B, is frequently expressed in human lung cancer tissues. The Spi-B-expressing cancer cells coexpressed vimentin but repressed E-cadherin and exhibited invasive behavior. Increased Spi-B expression was associated with tumor grade, lymphatic metastasis, and short overall survival. Mechanistically,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 51 publications
3
27
0
Order By: Relevance
“…8B,C). Consistent with our previous observation, autophagy deficiency increases CLDN2 protein levels and inhibits anchorage-independent cell growth [15]. Thus, these data indicate that SPIB-mediated transcriptional regulation is involved in anoikis resistance in lung cancer cells.…”
Section: Spib Enhances Snap47 Transcription Upon Matrix Deprivationsupporting
confidence: 92%
“…8B,C). Consistent with our previous observation, autophagy deficiency increases CLDN2 protein levels and inhibits anchorage-independent cell growth [15]. Thus, these data indicate that SPIB-mediated transcriptional regulation is involved in anoikis resistance in lung cancer cells.…”
Section: Spib Enhances Snap47 Transcription Upon Matrix Deprivationsupporting
confidence: 92%
“…This tool revealed that rs6953766 creates a binding site for Spi-B transcription factor. It is an Ets family TF expressed exclusively in mature B cells, T-cell progenitors and plasmacytoid dendritic cells (30). Nevertheless, Jian et al (31) reported that Spi-B is one of the twenty TFs overexpressed in GC tumors compared to normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Jian et al (31) reported that Spi-B is one of the twenty TFs overexpressed in GC tumors compared to normal tissues. Recently, Du et al (30) published the results of a study of this TF in NSCLC tumors. They found that high Spi-B expression is associated with worst prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…37 The third gene SPIB, encoding an ETS-domain transcription factor, was believed to be associated with cancers especially in lymphomas. 38,39 Also, Yi-Jung et al 40 found the SPIB may be involved in tumorigenesis in live cancer, and Wei et al 41 reported that SPIB is expressed in invasive cancer cells in human primary lung cancer tissues. ALDH3B2 was widely known as a member of aldehyde dehydrogenases (ALDHs).…”
Section: Discussionmentioning
confidence: 99%